2006
DOI: 10.1111/j.1348-0421.2006.tb03844.x
|View full text |Cite
|
Sign up to set email alerts
|

Typing of bfpA Genes of Enteropathogenic Escherichia coli Isolated in Thailand and Japan by Heteroduplex Mobility Assay

Abstract: We developed a rapid genetic approach for screening bfpA variants of enteropathogenic E. coli (EPEC) using a heteroduplex mobility assay (HMA). A total of 204 human EPEC strains were isolated in Thailand and Japan. Of 34 bfpA‐positive EPEC strains, bfpA variants were classified into 5 HMA‐types. Different HMA‐types were found in EPEC of the same serotypes. The results suggest that HMA is a simple and easy method to analyze polymorphism of bfpA gene, and can be used in laboratories without large apparatus such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…For detection of enteric bacteria, real-time multiplex PCR with primers and probes, described previously ( 20 ), was used for detection of ipaH , invA , aggR , eae , STh, STp , and LT genes to detect Shigella species/enteroinvasive E. coli (EIEC), Salmonella species, enteroaggregative E. coli (EAEC), atypical enteropathogenic E. coli (EPEC), STh and STp heat-stable toxin–producing enterotoxigenic E. coli (ST-ETEC), and heat-labile toxin–producing ETEC (LT-ETEC). We modified primers published by Iida et al ( 21 ) and designed new probes to detect bfpA genes for typical EPEC. For detection of cadF genes for Campylobacter jejuni , primers and probes published by Elfving et al ( 22 ) were used.…”
Section: Methodsmentioning
confidence: 99%
“…For detection of enteric bacteria, real-time multiplex PCR with primers and probes, described previously ( 20 ), was used for detection of ipaH , invA , aggR , eae , STh, STp , and LT genes to detect Shigella species/enteroinvasive E. coli (EIEC), Salmonella species, enteroaggregative E. coli (EAEC), atypical enteropathogenic E. coli (EPEC), STh and STp heat-stable toxin–producing enterotoxigenic E. coli (ST-ETEC), and heat-labile toxin–producing ETEC (LT-ETEC). We modified primers published by Iida et al ( 21 ) and designed new probes to detect bfpA genes for typical EPEC. For detection of cadF genes for Campylobacter jejuni , primers and probes published by Elfving et al ( 22 ) were used.…”
Section: Methodsmentioning
confidence: 99%
“…The absence of the Shiga toxin gene (stx) was determined by the methods of Karch and Meyer (17) and Etoh et al (8). The bfpA gene was confirmed using the primer set bfpAks/bfpAkcomas2 and the methods of Iida et al (14).…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported 5 HMA‐ bfpA types (34). In this study, we identified a new type, HMA‐ bfpA type 6 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The typing of eae and bfpA was performed by HMA as previously described (34, 35). HMA is a convenient way of determining the similarity of sequences from their heteroduplex mobility in polyacrylamide gel electrophoresis (36).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation